The impact of quality management practices towards digital transformation readiness in the food industry - Abdul Halim Lim, Sarina; Ismail, Ahmad Fareed; M.A., Saryatmo (Asian Scholars Network, 2024)
This study investigates the influence of quality management practices (QMP) on digital transformation (DT) readiness within the food industry. A quantitative research approach was adopted, employing an online explanatory questionnaire distributed to 129 executives, senior managers, and quality managers in the food sector. Data analysis involved descriptive statistics, reliability analysis, multiple regression analysis, path analysis, and t-test analysis using SPSS and SmartPLS software. The findings reveal that most food companies implement QMP through certified programs like HACCP and ISO 9001. Current DT readiness in the industry is at an intermediate level (μ = 3.747), with larger companies demonstrating higher readiness (μ = 4.633). Importantly, a positive causal relationship exists between QMP and DT readiness (p < 0.01). While the study provides valuable insights, future research could explore the specific QMP elements most impactful on DT readiness within the food industry. Additionally, a broader geographical scope could enhance generalizability. The findings suggest that robust QMP fosters DT readiness in the food industry. This knowledge can guide companies in strengthening their quality management systems to facilitate successful digital transformation initiatives. This study contributes novel insights by exploring the link between QMP and DT readiness within the under-investigated context of the food industry. The results provide valuable guidance for food businesses aiming to leverage digital technologies while maintaining high-quality standards.